Clinical effects of unilateral biportal endoscopic decompression for lumbar posterior apophyseal ring separation - Liu, Jianjun; Zhu, Bin; Chen, Lei; Jing, Juehua; Tian, Dasheng (Frontiers in Surgery, 2022)
Abstract Objective: The purpose of the study was to investigate the feasibility and effects of unilateral biportal endoscopic decompression for lumbar posterior apophyseal ring separation(PARS). Methods: Patients with lumbar PRAS who received unilateral biportal endoscopic decompression from June 2020 to September 2021 were analyzed, including 11 females and 15 males.The clinical symptoms were consistent with the imaging findings.Operation time, length of postoperative hospital stay and complications were recorded, and the clinical efficacy was evaluated by Visual Analogue Scale (VAS), Oswestry Disability Index (ODI) and modified Macnab scale at preoperative, postoperative 1, 3, 6 months and the last follow-up. Results: Preoperative VAS scores of low back pain were (5.04±1.37) and respectively decreased to (2.81±0.75) ,(2.35±0.98) ,(1.65±0.69)and (1.15±0.68) at postoperative 1,3 ,6months and at the last follow-up, and the difference was statistically significant ( F =127.317，P=0.000) . Preoperative VAS scores of lower limb pain were (6.92±1.38) and respectively decreased to (2.88±1.07) ,(2.54±1.03) ,(1.81±0.80)and (1.00±0.69) at postoperative 1,3 ,6months and at the last follow-up, and the difference was statistically significant ( F =285.289，P =0.000 ) .Preoperative ODI scores were (60.47±8.89) and respectively decreased to (34.72±4.13) ,(25.80±3.65) ,(17.71±3.41)and (5.65±2.22) at postoperative 1,3 ,6months and at the last follow-up, and the difference was statistically significant ( F =725.255，P =0.000 ) . According to the modified Macnab criteria, the final outcome was excellent in 22 cases, good in 3 cases, fair in 1 cases. 26 patients could return to work or normal activities within 3 weeks. Conclusions: Unilateral biportal endoscopic decompression has the advantages of clear and wide field of vision, large operating space, relatively simple need of surgical instrument and convenient and flexible operation procedure.It can achieve excellent clinical results with favorable efficacy and safety and may become a new minimally invasive endoscopic treatment for lumbar PARS.